2020
DOI: 10.3892/ol.2020.11508
|View full text |Cite
|
Sign up to set email alerts
|

Combination of pembrolizumab and 125I attenuates the aggressiveness of non‑small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer-associated mortality. Therapies targeting programmed cell death 1 ligand 1 (PD1L1) have promising effects on NSCLC. However, resistance to targeted therapy has become the main problem and the underling molecular mechanism remains unclear. In the present study, the expression of PD1L1 in NSCLC was determined and the association with clinicopathological characteristics was analyzed. A combination therapy was also constructed, including pembrolizum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Notably, the in ltrating immune cells consist of various lymphocytes that can attack the tumor cells or help the tumor cells survive the host immune system [39]. Previously, we reported that PD-L1/PD1 were highly expressed in NSCLC and combination of pembrolizumab and 125I attenuates the aggressiveness of this disorder [40]. Both PD-L1/PD1 and OLFML2B could construct the immunosuppressive microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the in ltrating immune cells consist of various lymphocytes that can attack the tumor cells or help the tumor cells survive the host immune system [39]. Previously, we reported that PD-L1/PD1 were highly expressed in NSCLC and combination of pembrolizumab and 125I attenuates the aggressiveness of this disorder [40]. Both PD-L1/PD1 and OLFML2B could construct the immunosuppressive microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Third, Treating each site can reduce cancer genetic diversity, delaying progression due to emergence of treatment-resistant clonogens and further seeding from the metastatic sites(Turajlic and Swanton 2016). Fourth, 125 I seed brachytherapy may bolster antitumor immune-mediated effect by promoting cancer antigen presentation and lymphocytic tumor in ltration(Wang et al 2020). Finally,we used chemotherapy plus immunotherapy before 125 I seed implantation, such design can select for patients with an intrinsically more indolent disease trajectory or tumors more sensitivity to systemic therapy because any patients whose cancer had progressed during systemic therapy would have been excluded from the trail.…”
mentioning
confidence: 99%